Dimensions of Openness: Beyond the Course as an Open Format in Online Education - Dalsgaard, Christian; Thestrup, Klaus (International Review of Research in Open and Distributed Learning, 2015)
The objective of the paper is to provide a framework for understanding the pedagogical opportunities of openness in education. The paper will argue that openness in education should not only be viewed as opening existing resources and courses to a broader audience. Openness is also a matter of providing insight and enable communication and collaboration across traditional barriers – such as distance and accessibility. From this perspective, openness is the removal of barriers for interaction and exchange – and not only a matter of providing access to resources or courses. Rather, the objective is to open education to the outside world, which entails an interaction between educational institutions and society. The key point of the paper is that to do this, educational activities need to change and move beyond the course as the main unit of openness. Openness is not only a matter of opening up the existing, but to develop new educational practices that interact with the world. The paper outlines three different dimensions of openness that describe different types of interaction between institutions and society: transparency, communication and engagement. To exemplify the dimensions, the paper presents a case study that demonstrates the three dimensions of openness in an university programme. The paper concludes in a discussion of educational technologies for the different dimensions of openness.